Walk them or no leg to stand on! Diagnostic delay of neurologic conditions in young children. (23rd May 2016) - Stock, Amanda; Dunn, Karen; Cheek, John A
Abstract: Diagnosis of low incidence neurological conditions can be a challenge in paediatric emergency medicine. Neurological examination in young children can be very difficult, and medical staff may not previously have encountered conditions like acute demyelinating encephalomyelitis. We propose that the simple process of walking a child (provided they were previously ambulant) is the crucial step in the neurological examination. We present three cases to demonstrate this important part of the examination.